From Ethological Linguistics to Animal Linguistics and Ecolinguistics - Augustyn, Prisca (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2018)
Biosemiotics and biolinguistics share some common origins in comparative psychology and ethology, both viewing language as a species-specific cognitive capacity whose main purpose is not communication but thought. From this perspective, biosemiotics should be at the center of cognitive science. However, biolinguistics and biosemiotics (or linguistics and semiotics) have been marginalized in the context of cognitive science and neuroscience; nonetheless there are currents in mainstream linguistics and cognitive science operating from a biosemiotic perspective without overtly articulating their research agendas as such. I believe that the future success of the biosemiotic movement will depend on recognizing and connecting with those research agendas.